Clinical Characteristics and Mid-Term follow-up of Elderly Patients with Severe Aortic Stenosis not Eligible for TAVI - Rezende,Mariana Oliveira (2021)
Abstract Background: The treatment for symptomatic severe aortic stenosis (AS) is the correction of valve stenosis by surgical valve replacement and more recently by transcatheter aortic valve implant (TAVI). However, in some high risk surgical patients, TAVI is not possible for technical or clinical reasons or due to the unavailability of the endoprosthesis. Objective: The aim of this study was to evaluate a mid-term follow-up of symptomatic severe AS patients who are not eligible for TAVI trials, as well as to identify the clinical features of these patients. Methods: This was an observational, retrospective study conducted with 475 symptomatic severe AS patients, evaluated by the Heart Team between 2000 and 2017. Inclusion criterias were: patients considered not to be eligible for TAVI. The Shapiro-Wilk test was applied to evaluate normality. Non-paired t and Mann-Whitney tests were applied for continuous variables, while the chi-squared and Fischer exact tests were applied for categorical variables, with a level of significance of p<0,05. Results: The heart team evaluated 475 patients: 25 (5.26%) died before any intervention could be proposed; 326 (68.3%) were submitted to TAVI, so the study population consisted of 124 patients not eligible for TAVI. Of these, 31 (25%) underwent surgery and 93 (75%) remained in clinical treatment. In a mean 56 months- follow-up the mortality in clinical group was 46.2%. In the surgical group the mortality was 23.9% (in-hospital 12.9% and late mortality 11% in a mean 47.4 months follow-up). The patients that died presented a significantly lower left ventricle ejection fraction (LVEF), a smaller valve area, and a larger end-systolic diameter of the LV. Conclusion: The mortality of the clinical group's patients was significantly higher than the surgical mortality (46.2% vs. 12.9%; p=0.021). The patients of the clinical group were older, weighed less, and had a higher incidence of renal failure and a higher STS score.